(untitled) (Develop, 2025)
This study aims to analyze the effect of education as measured by the average length of schooling on income inequality as measured using the gini ratio in six Provinces in Java Island during the period 2007-2024. The method used in this study is panel data regression with a fixed effect model/FEM approach. The results of the study indicate that the average length of schooling has a significant positive effect on income inequality, which indicates that the distribution of education in the study area is not yet even, so it actually encourages an increase in income inequality. This is in line with the Kuznets hypothesis, where in the early stages of development, increasing education that is not yet inclusive can increase inequality. This study emphasizes the importance of equalizing access and quality of education so that the role of education as a tool for income equality can be realized.